KRAS MUTATIONS IN PANCREATIC ADENOCARCINOMA IN CORRELATION WITH CLINICAL AND PATHOLOGICAL CHARACTERISTCS - Trpchevska, Emilija Nikolovska; Jovanovska, Rozalinda Popova; Petrushevska, Gordana; Eftimov, Aleksandar; Nikolova, Dafina; Nikolovska, Ance Volkanovska (Journal of Morphological Sciences; Vol 3 No 1 (2020): JMS, 2020)
Pancreatic adenocarcinoma is the seventh cause of death of all malignant tumors worldwide and has the worst prognosis of all solid tumors. In Europe, it is the sixth most common cause of cancer related death and in United States it is the fifth cause of death after lung cancer, prostate cancer, breast and colorectal cancer. Numerous molecular studies have analyzed genetic and epigenetic changes as responsible for the histological variants of this cancer, their correlation with family predisposition, and opportunities for better treatment and survival. This study included 42 patients with pancreatic adenocarcinoma. Tumor tissue samples obtained from surgical specimen were histopathologicaly examined and genetic mutations were determinate. Prior to surgery, patients were diagnosed by imaging modalities (abdominal ultrasound and/or CT), clinical and laboratory examinations. Histopathological analyses included: T category, grade of tumor differentiation, vascular invasion, lymph node involvement and metastasis. We obtained the KRAS and EGFR gene mutations on the Randox investigator diagnostic platform.The aim of the study was to determine the frequency of KRAS and EGFR mutations in pancreatic adenocarcinoma and their correlation with multiple tumor characteristics. No one patient had EGFR mutation. The results showed that more of the patients with KRAS genetic mutations are frequently associated with advanced disease stage and worse prognosis, although the difference was not statistically significant in comparison to patients without KRAS mutations.  Key words:pancreatic adenocarcinoma, KRAS, EGFR.